Giant invasive Heracleum persicum: Friend or foe of plant diversity? - Rijal, Dilli Prasad; Alm, Torbjørn; Nilsen, Lennart; Alsos, Inger Greve (Ecology and Evolution, 2017)
Source at https://dx.doi.org/10.1002%2Fece3.3055 The impact of invasion on diversity varies widely and remains elusive. Despite the con- siderable attempts to understand mechanisms of biological invasion, it is largely un- known whether some communities’ characteristics promote biological invasion, or whether some inherent characteristics of invaders enable them to invade other com- munities. Our aims were to assess the impact of one of the massive plant invaders of Scandinavia on vascular plant species diversity, disentangle attributes of invasible and noninvasible communities, and evaluate the relationship between invasibility and ge- netic diversity of a dominant invader. We studied 56 pairs of Heracleum persicum Desf. ex Fisch.- invaded and noninvaded plots from 12 locations in northern Norway. There was lower native cover, evenness, taxonomic diversity, native biomass, and species richness in the invaded plots than in the noninvaded plots. The invaded plots had nearly two native species fewer than the noninvaded plots on average. Within the in- vaded plots, cover of H. persicum had a strong negative effect on the native cover, evenness, and native biomass, and a positive association with the height of the native plants. Plant communities containing only native species appeared more invasible than those that included exotic species, particularly H. persicum . Genetic diversity of H. per - sicum was positively correlated with invasibility but not with community diversity. The invasion of a plant community by H. persicum exerts consistent negative pressure on vascular plant diversity. The lack of positive correlation between impacts and genetic diversity of H. persicum indicates that even a small founder population may cause high impact. We highlight community stability or saturation as an important determinant of invasibility. While the invasion by H. persicum may decrease susceptibility of a plant community to further invasion, it severely reduces the abundance of native species and makes them more ...